FENOMENA PENGGUNAAN BAHASA SLANG DI KONTEN MARAPTHON DALAM MENEMUKAN IDENTITAS DIRI REMAJA SMA SANDIKTA - Delfi Putri; Sari Ekowati (Tamilis Synex: Multidimensional Collaboration, 2026)
The rapid development of social media, particularly YouTube, has influenced adolescents’ communication patterns through the widespread use of slang in everyday interactions. One notable phenomenon is the use of slang in marathon content on the @YB YouTube channel, which has become popular among teenagers as a means of self-expression, identity formation, and social bonding. This study aims to examine the phenomenon of slang language usage in marathon content on the @YB YouTube channel and its role in shaping the self-identity of Grade XI F1 students at Sandikta Senior High School. This research employs a qualitative approach using the phenomenological method within a constructivist paradigm. Data were collected through in-depth interviews, observations, and documentation involving students who met the research criteria. The data were analyzed through data reduction, data presentation, and conclusion drawing. The expected findings indicate that the use of slang is influenced by the intensity of watching marathon content on the @YB YouTube channel, peer interactions, and digital communication culture. Furthermore, slang functions not only as a communication tool but also as a medium for developing self-identity, strengthening group solidarity, and expressing adolescents’ social identities in their daily lives.